Analisis Kemampuan Guru dalam Menanamkan Kemampuan Pemahaman Konsep dan Mengembangkan Kemampuan Pemecahan Masalah terhadap Hasil Belajar Siswa - Nesti Surya Astuti Zebua; Alianus Zalukhu; Herman Herman; Doni Berkat Tabah Hulu; Hardi Tambunan; Firman Pangaribuan (Journal on Education, 2023)
This study aims to determine the category of mathematics teacher's ability to build the ability to understand concepts and instill mathematical problem solving abilities on student learning outcomes. This research was conducted at SMA Negeri 1 Alasa, and the sample was taken randomly as many as 272 students. The research instrument used a questionnaire, and data analysis used descriptive analysis. Based on the results of the analysis it can be concluded that the ability of mathematics teachers to build understanding of concepts and instill mathematical problem solving abilities on student learning outcomes in the moderate category.